The Effect of Ad Model Ethnicity on Advertising - Haryadi Arief Nuur Rasyid (Komunikator, 2019)
This research focuses on the use of ad models ethnicity in advertising. Researcher using laboratory experimental method with 2x2 between-subjet factorial design. The factors are manipulated is ad models ethnicity (Chinese ad model versus Javanese ad model) and product ethnic category (Chinese ethnic product versus Javanese ethnic product). Participants used is 160 female students from SMA Steladuce 1 Yogyakarta.     The results showed that the presence of Chinese ethnic minority in the environment of Javanese ethnic majority led to individuals from Chinese ethtnic minority become more sensitive to referencing themselves to advertisement with Chinese model (H-1). The results of this research also shows that individual’s self referencing to the advertisement with model that fits with  individual's ethnicity may affect individual attitude in advertising (H-2a, H-2b, H-2c). Further results from this study indicate that the existence of the Javanese ethnic product can moderate self referencing of  individual consumers to advertisement that use model from Chinese ethnic minority (H-3a and H-3b)